2020
DOI: 10.1071/bt19131
|View full text |Cite
|
Sign up to set email alerts
|

Testing the impact of community composition on the productivity of a cool temperate eucalypt forest: the Australian Forest Evenness Experiment (AFEX)

Abstract: Understanding the factors controlling productivity is crucial for modelling current and predicting future forest growth and carbon sequestration potential. Although abiotic conditions exert a strong influence on productivity, it is becoming increasingly evident that plant community composition can dramatically influence ecosystem processes. However, much of our understanding of these processes in forests comes from correlative studies or field experiments in short-statured, short-lived vegetation. Here, we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Eucalypt seeds were not pretreated before sowing due to already high germination rates. Seeds were sown at a target community density of 20 potential germinants m −2 but some variation exists between the realised and sown composition of each treatment (Table S1; Gerwin et al ., 2020). Acacia dealbata is under‐represented due to lower‐than‐expected germination success and severe browsing of seedlings in the first year.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eucalypt seeds were not pretreated before sowing due to already high germination rates. Seeds were sown at a target community density of 20 potential germinants m −2 but some variation exists between the realised and sown composition of each treatment (Table S1; Gerwin et al ., 2020). Acacia dealbata is under‐represented due to lower‐than‐expected germination success and severe browsing of seedlings in the first year.…”
Section: Methodsmentioning
confidence: 99%
“…The AFEX (Gerwin et al, 2020) occupies a 5 ha site in the Styx Valley, southern Tasmania (42°46 0 49″S, 146°49 0 01″E; Fig. 1) at an altitude of 530-590 m above sea-level on a north-west facing slope.…”
Section: Study Site and Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…We used tree growth data from the Australian Forest Evenness Experiment (AFEX; Gerwin et al, 2020) to demonstrate how neighbour indices can be correctly incorporated into a regression analysis of tree growth. The AFEX is a cool temperate experimental forest established in April 2013 with seeds of four locally dominant native tree species: Eucalyptus delegatensis , E. regnans , Pomaderris apetala and Acacia dealbata .…”
Section: Methodsmentioning
confidence: 99%
“…Here, we explored how neighbouring plants impacted annual growth in two eucalypts, Eucalyptus delegatensis and Eucalyptus regnans , over a three‐year period in the Australian Forest Evenness Experiment (AFEX; Gerwin et al., 2020) in south‐east Tasmania, Australia. Previous work in the system has shown that the two eucalypts are sensitive to drought‐induced canopy damage, and that damage is exacerbated at high densities of certain species, particularly in E. delegatensis (Britton et al., 2022).…”
Section: Introductionmentioning
confidence: 99%